Strategic plan of Brazilian Table Tennis Confederation: looking for development - Campestrini, G. R. H. (Proceedings Book of The 16th ITTF Sports Science Congress Budapest (HUN), April 19th - 20th, 2019, 2020)
The Brazilian Table Tennis Confederation (CBTM) has systematically advanced in the modernization of its management and is attentive to the new demands of the sport market. According to these premises, in 2016 CBTM developed a strategic plan that could allow institutional orientation for the new challenges of modern sport. The planning methodology consisted of documental study, semistructured interviews, workshops and benchmark with main reference cases of sport and entertainment. The result was the redesign of functions and institutional approach from the year 2017, with KPIs measurement. The organizational structure was based on 6 major areas: (1) International Talents, linked to the Brazilian team; (2) National Talents, linked to competitions and the Brazilian ranking; (3) Table Tennis for Leisure, associated with table tennis enthusiasts; (4) Marketing and Business, connected to communication, media, sponsorship and relationship with fans; (5) Corporate University, focused on the training and promotion of knowledge; (6) Management and Governance, oriented to the administrative aspects of the entity. From this strategic plan, CBTM begins to reach a differentiated level, both nationally and internationally, with the expectation of consolidating a sustainable management model for the future.